KUZMAN SHAPKAREV’S BIOGRAPHY IN THE CONTEXT OF BIOGRAPHICAL DISCOURSES - Tasevska Hadji Boshkova, Iskra (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Biographical discourse is characterized by its unique and broader significance in correlation with autobiographical forms. According to Smith and Watson, the most important difference between biography and autobiography lies in the biographical point of view, which is positioned outwardly (i.e. that of the biographer), and that correspondingly defines the subject and this writing focused upon him. In one hand, it is quite a relief for the reader to freely distinguish the narrator and the character (which is not the case in autobiography), but on the other the biographer is unable to create an intimate relation with the past experiences, so he is viewing the events from the perspective of common people. The subject of our analysis is Kuzman Shapkarev’s biography of Brothers Miladinov, a form that once again underlines the means by which the biographical and the autobiographical are being combined. Considering the fact that Shapkarev is also an author of two autobiographies, we can state that in the 19th century Macedonian literature biographical description cannot be established without the author’s deep (emotional, but also ideological, ethical) connection with the represented character and its work (especially considering the literary biography). Keywords: biography, Shapkarev, 19th century Macedonian literature, discourse, biographical subject.